Saving Alberta's Resource Revenues: Role of Intergenerational and Liquidity Funds - Ton S. van den Bremer; Rick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2016)
We use a welfare-based intertemporal stochastic optimization model and historical data to estimate the size of the optimal intergenerational and liquidity funds and the corresponding resource dividend available to the government of the Canadian province Alberta. To first-order of approximation, this dividend should be a constant fraction of total above- and below-ground wealth, complemented by additional precautionary savings at initial times to build up a small liquidity fund to cope with oil price volatility. The ongoing dividend equals approximately 30 per cent of government revenue and requires building assets of approximately 40 per cent of GDP in 2030, 100 per cent of GDP in 2050 and 165 per cent in 2100. Finally, the effect of the recent plunge in oil prices on our estimates is examined. Our recommendations are in stark contrast with historical and current government policy.
Keywords: E21; E22; D91; Q32; 330; oil price volatility; precautionary saving; resource wealth; fiscal policy